2021
DOI: 10.1093/ejcts/ezab507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of minimally invasive mitral valve surgery compared to sternotomy on short- and long-term outcomes: a retrospective multicentre interventional cohort study based on Netherlands Heart Registration

Abstract: OBJECTIVES Minimally invasive mitral valve surgery (MIMVS) has been performed increasingly for the past 2 decades; however, large comparative studies on short- and long-term outcomes have been lacking. This study aims to compare short- and long-term outcomes of patients undergoing MIMVS versus median sternotomy (MST) based on real-world data, extracted from the Netherlands Heart Registration. METHODS Patients undergoing mitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
3
23
1
Order By: Relevance
“…However, mortality is reported to range up to 11.1% in the Society of Thoracic Surgeons (STS) database [ 13 ], which is based on a multicentre registry, potentially more accurately reflecting real-world results. In accordance with a prior comparison between MIMVS and sternotomy in primary MV surgery of the Dutch national registry, no difference in 30-day mortality regarding surgical approach was observed [ 14 ]. Of note, in a previous meta-analysis by our research group, a significant early mortality benefit of the MIMVS approach in a reoperative setting was found [ 9 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, mortality is reported to range up to 11.1% in the Society of Thoracic Surgeons (STS) database [ 13 ], which is based on a multicentre registry, potentially more accurately reflecting real-world results. In accordance with a prior comparison between MIMVS and sternotomy in primary MV surgery of the Dutch national registry, no difference in 30-day mortality regarding surgical approach was observed [ 14 ]. Of note, in a previous meta-analysis by our research group, a significant early mortality benefit of the MIMVS approach in a reoperative setting was found [ 9 ].…”
Section: Discussionsupporting
confidence: 77%
“…In terms of morbidity and complication rate, a low incidence of major postoperative complications for both repeated sternotomy as MIMVS was observed. As known from other large registries and a recent analysis of primary MV surgery [ 14 ], MV surgery through a minimally invasive approach is associated with a lower incidence of new-onset postoperative arrythmia compared to sternotomy. This finding is confirmed in the current analysis of patients undergoing reoperative procedures and is potentially explained by less need of adhesiolysis, less cardiac manipulation and a subsequent reduction in inflammation [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite many studies that included a large number of patients undergoing MIMVS, there is still debate regarding the superiority of a particular mini-access route and even conventional sternotomy [ 71 ]. A recent study which included the same mitral valve surgery data from the NHR concluded that based on an analysis of registry data there was no reason to assume superiority of MIMVS in general [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal results have been published, but data from the real world have not been extensively reported. A recent Nationwide survey 16 analyzed the outcome in 2,501 patients who underwent MVr between 2013 and 2018 through different approaches. In propensity score matched groups (718 each) the Authors found that patients undergoing MVr through a right mini-thoracotomy had a lower rate of repair (76.3% versus 80.9%, p=0.04).…”
mentioning
confidence: 99%